Continuous Glucose Monitoring Enabled by Fluorescent Nanodiamond Boronic Hydrogel. Issue 7 (16th January 2023) - Zhang, Jian; Zheng, Yongjun; Lee, Jimmy; Hoover, Alex; King, Sarah Ann; Chen, Lifeng; Zhao, Jing; Lin, Qiuning; Yu, Cunjiang; Zhu, Linyong; Wu, Xiaoyang
Abstract: Continuous monitoring of glucose allows diabetic patients to better maintain blood glucose level by altering insulin dosage or diet according to prevailing glucose values and thus to prevent potential hyperglycemia and hypoglycemia. However, current continuous glucose monitoring (CGM) relies mostly on enzyme electrodes or micro‐dialysis probes, which suffer from insufficient stability, susceptibility to corrosion of electrodes, weak or inconsistent correlation, and inevitable interference. A fluorescence‐based glucose sensor in the skin will likely be more stable, have improved sensitivity, and can resolve the issues of electrochemical interference from the tissue. This study develops a fluorescent nanodiamond boronic hydrogel system in porous microneedles for CGM. Fluorescent nanodiamond is one of the most photostable fluorophores with superior biocompatibility. When surface functionalized, the fluorescent nanodiamond can integrate with boronic polymer and form a hydrogel, which can produce fluorescent signals in response to environmental glucose concentration. In this proof‐of‐concept study, the strategy for building a miniatured device with fluorescent nanodiamond hydrogel is developed. The device demonstrates remarkable long‐term photo and signal stability in vivo with both small and large animal models. This study presents a new strategy of fluorescence based CGM toward treatment and control of diabetes. Abstract : Continuous glucose monitoring (CGM) allows diabetic patients to better maintain blood glucose level. In this proof‐of‐concept study, a skin mountable device is developed with fluorescent nanodiamond hydrogel, presenting a new strategy of fluorescence based CGM toward treatment and control of diabetes.